Analisis Kesulitan Siswa SD dalam Memahami Soal Cerita Matematika pada Operasi Hitung Perkalian dan Pembagian - Marzuqo, Khusnal; Khairani, Annisa; Indrawanis, Indrawanis; Hasibuan, Nuryadani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to identify the difficulties experienced by third-grade students at SDIT Insan Madani in understanding multiplication and division material in Mathematics. The research employed a descriptive qualitative approach, with data collected through observations and interviews with both students and the classroom teacher. The research sample consisted of 27 third-grade students. The results revealed that students encountered various difficulties in solving word problems related to multiplication and division operations. These difficulties included: misunderstanding the content of the problems (66.7%), which was mainly due to a lack of ability to comprehend narratives and identify key information; incorrect selection of mathematical operations (77.8%), caused by a weak understanding of multiplication and division concepts; and procedural errors in calculations (74.1%), resulting from the students’ lack of mastery in following proper calculation steps. Internal factors contributing to these difficulties included fear and low self-confidence, while external factors involved the use of less contextual learning approaches and a lack of practice with word problems.